Fatores de risco e análise espacial da infecção por Schistosoma mansoni em escolares de área endêmica no estado de Sergipe, Brasil - Leal, Iane Brito (2018)
Schistosomiasis mansoni is a transmissible, chronic and severe parasitic disease caused by Schistosoma mansoni. It is one of the most prevalent parasitic diseases in the world. In Brazil, it represents an important public health problem, especialy in the Northeast of the country, where the disease is historically endemic. Sergipe is one of the states with the highest prevalence and average positive rate above the national medium. This study aimed to analyze the risk factors and the spatial pattern of schistosomiasis in schoolchildren from the endemic area of the state of Sergipe, Brazil. It is an epidemiological, descriptive and cross-sectional study with spatial analysis techniques. The research was carried out in four moments: a) community awareness and research participants in three schools; b) collection of faeces and urine samples; c) spatial location in the households of the research participants with the aid of a receiver to locate the geographical coordinates; d) application of a questionnaire to survey the socioeconomic, behavioral, environmental and contact factors associated with the occurrence and transmission of the disease. In the analysis of the descriptive data the Microsoft Excel 2007 program was used. The spatial analysis of the distribution of the infection in the municipality was carried out through the software GPS TrackMaker and QGIS 2.18.16 using the Kernel intensity estimator. Statistical analysis was performed using Chi-square test and prevalence ratio. A total of 73 cases were identified using the Kato-Katz method (KK) and 100 cases with the method Catódico Circulante Antigen (POC-CCA) in the study. We found that the percentage of positivity for schistosomiasis mansoni was 23.7% (KK) and 32.46% (POC-CCA); in relation to the gender of the S. mansoni infected subjects, the male sex prevailed and the most affected age group was 11 to 16 years of age, in both methods. The mild infection prevailed with 65.8%, according to the parasitic load. The individuals most at risk for schistosomiasis infection are male, those living in a rural area, in their own home, near the springs, with their residences accumulating water in the yard in the summer and winter, with artesian well, in unpaved streets, where individuals step on street water in summer and winter, which has constant contact with waters. The spatial analysis points to the existence of three large clusters, one in the urban zone and two in the rural area, and the visualization of areas with a higher concentration of cases exposed to different degrees of risk. The results of the research allow a better understanding of the reality of the disease, and thus facilitate the understanding of the spatial distribution of schistosomiasis mansoni.